Pengembangan Usaha Pengelolaan Sampah Pada Badan Usaha Milik Desa (BUMDes) Sinergi Kabupaten Purwakarta dengan Business Road Map - Akhmad Solikin; Ivan Yulianto; Sakti Prabowo (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
Waste is an environmental problem which has been urgent to solve, including in Purwakarta District which are implementing several programs to overcome it. One of the programs is waste bank which is implemented by community organizations. This article analyses a business plan for waste management managed by Village-Owned Enterprise (BUMDes) Sinergi, Purwakarta District. Data collection methods were interviews, field observations, comparative study, and literature studies. Data analysis for business development strategy was using Business Road Map (BRM). Research succeeded to identify fifteen elements of BRM. BUMDes Sinergy in the early steps is advised to focus on collecting and sorting inorganic waste, especially plastic waste which is more expensive, by implementing waste to charity and waste bank mechanisms. In the medium term, business could be developed by processing organic waste to fertilizer and inorganic waste to plastic ore or upscaling waste to recycled products which have higher value added.